The Design and Application for Electric Drive System of HXD1C Locomotive - 高首聪; 刘可安; 李鹏 (机车电传动)
The design concept and major parameters of electric drive system of the HXD1C locomotive was introduced. The test and application of the electric drive system were described, which showed that the design was reasonable and reliable, meeting the design requirement.